4∛16+5-∛54-8∛2=
√72+3√32-4√12-7√18+4√75=
6√20-√24+2√125-√80+⅗√150=
4∛3+∛24-5∛81=
√√100+√36=
√5√5√25=
(3√27-2√12-4√75)/√3=
(4√0,54-5√0,06-4√0,0014+2√0,24)/√6=
(2∛0,0024-4∛0,003+3∛0,081)/∛3=
(√8-√72)/√2
∛6*∛9*∛4=
∛3*∛18/∛16=
√20+√45-2√125=
√3*(4√3-5√12-2√27)=
(√12-10√147-√75)/√3=
√108-4√3=
√50-√242+√98=
10∛2-∛54+12∛16=

2

Odpowiedzi

2009-11-09T22:17:29+01:00
4∛16+5-∛54-8∛2=(-35)
4∛3+∛24-5∛81=(-51)
∛6*∛9*∛4=216
10∛2-∛54+12∛16= (-36)
tylko te przyklady wiem i nie wiem czy sa doberze ale chyba tak ;)
Najlepsza Odpowiedź!
2009-11-09T22:40:08+01:00
4∛16+5-∛54-8∛2=4∛8*2+5-∛27*2-8∛2=8∛2+5-3∛2-8∛2=-3∛2+5

√72+3√32-4√12-7√18+4√75= √36*2+3√16*2-7√9*2+4√25*3= 6√2+12√2-21√2+20√3= -3√2+20√3

6√20-√24+2√125-√80+⅗√150= 6√5*4-√6*4+2√25*5-√16*5+⅗√25*6= 12√5-2√6+10√5-4√5+3√6= 18√5+√6

4∛3+∛24-5∛81= 4∛3+∛8*3-5∛27*3= 4∛3+2∛3-15∛3= -9∛3

√√100+√36=tego przykłady nie wiem

√5√5√25=√5*5*25=√625≡25

(3√27-2√12-4√75)/√3=(3√9*3-2√4*3-4√25*3)/√3= (9√3-4√3-20√3)/√3= (-7√3)/√3= -7

(4√0,54-5√0,06-4√0,0014+2√0,24)/√6=tego nie wiem

(2∛0,0024-4∛0,003+3∛0,081)/∛3=tego nie wiem

(√8-√72)/√2= (√4*2-√36*2)/√2= (2√2-6√2)/√2= (-4√2)/√2=-4

∛6*∛9*∛4=∛6*9*4=∛216=6

∛3*∛18/∛16=(∛3*18)/∛8*2= (∛54)/2∛2= (∛27*2)/2∛2= 3∛2/2∛2=1,5

√20+√45-2√125=√4*5+√9*5-2√25*5=2√5+3√5-10√5=-5√5

√3*(4√3-5√12-2√27)=√3*(4√3-20√3-6√3)=√3*(-22√3)=-66

(√12-10√147-√75)/√3=(√4*3-10√49*3-√25*3)/√3= (2√3-70√3-5√3)/√3= (-73√3)/√3=-73

√108-4√3=√36*3-4√3=6√3-4√3=2√3
√50-√242+√98=√25*2-√121*2+√49*2= 5√2-11√2+7√2= √2

10∛2-∛54+12∛16= 10∛2-∛27*2+12∛8*2=10∛2-3∛2+24∛2=31∛3